Seasonal variation in susceptibility of the pear psyllid, Cacopsylla permixta (Hemiptera: Psyllidae) to selected insecticides. (29th April 2019) - Esmaeily, Mojtaba; Talebi, Khalil; Hosseininaveh, Vahid; Nozari, Jamasb
Abstract: Although Cacopsylla pyri Forster and Cacopsylla pyricola Linnaeus have long been considered as more significant pests of pear trees around the world, Cacopsylla permixta Burckhardt and Hodkinson is the most significant pest in some parts of Iran, especially in pear gardens of Karaj. Current control strategies against this pest in Iran generally involve five or six insecticide treatments each year, despite unsatisfactory results are reported at many localities. So, it is crucial to know the most susceptible generation of the pest to apply a good strategy for its control. The aim of this study was to explore the seasonal variation in susceptibility of C. permixta to four commonly used insecticides. The results showed that winter forms (February) were 2.71‐fold, 4.58‐fold, 3.26 fold and 3.38‐fold more tolerant to diazinon, imidacloprid, acetamiprid and abamectin, respectively, compared with summer forms. Also, Esterase, GST and P450 monooxygenase activity was highest during February. Moreover, the content of lipid, carbohydrate, glycogen and protein was significantly higher in February compared with other months. Based on these results, the best period for insecticide treatment for efficient control is treatment against the first generation, at the time when eggs are laid by females as well as during the egg hatching and the larvae appearance. At this time of year, psylla are more susceptible, which would likely lead to better results and the reduction in damage during the next summer. However, further studies are needed to test this in farm settings, and to whether this holds true for other psylla species.